The Government's Role in Empowering Farmer Groups in Kuta Baru Village, Tebing Tinggi District, Serdang Bedagai Regency - Ayu dwyanti, Sekar; Adil Mubarak (Jurnal Dialektika: Jurnal Ilmu Sosial, 2024)
This study aims to describe the role of the government in empowering farmer groups in Kuta Baru Village, Tebing Tinggi Subdistrict, Serdang Bedagai Regency. The objective of this research is to understand the government's role in empowering farmer groups in Kuta Baru Village. The research adopts a qualitative approach with a descriptive method. Informants were selected using purposive sampling, and data were obtained through interviews with research informants and direct observation in Kuta Baru Village, Tebing Tinggi Subdistrict, Serdang Bedagai Regency. The data is supported by documentation evidence and relevant documents available at the Kuta Baru Village Office.The data analysis process in this study involves data reduction, data presentation, drawing conclusions, and verification. The findings indicate that the government’s role in empowering farmer groups in Kuta Baru Village is not yet optimal. This is due to a lack of government attention to the farmer groups, insufficient active involvement by the government to address the challenges faced by the groups—such as funding issues, agricultural facilities, and infrastructure and the uneven distribution of aid. Moreover, much of the aid, such as plant seeds, is unsuitable for plantin.